Clément Marot e Renée di Valois stranieri in terra d’esilio. Riflessioni sulle rhymes marotiques ferraresi - Bianca Maria Giusto (Annali Online dell'Università di Ferrara. Sezione Lettere, 2016)
The essay analyzes the writings of the French poet Clément Marot during his exile in Ferrara caused by his religious position. The corpus includes twenty poems having as subject the struggle to be exiled in a foreign country. Those poems, dated between 1528 and 1536, and addressed to different recipients, allow a parallelism with the feelings of the duchess Renée of Valois, his protector who shared the same destiny.